Correlação da produtividade do feijão com a resistência à penetração do solo sob plantio direto - Carvalho, Guilherme J. [UNESP]; Carvalho, Morel de P. [UNESP]; Freddi, Onã Da S. [UNESP]; Martins, Mariana V. [UNESP] (FapUNIFESP (SciELO), 2006)
The soil mechanical resistance to penetration (PR) has great influence on vegetative development as the root growth and the crop productivity change in inverse proportion. Thus, the objective of this research was to study correlation between the bean grain productivity and the PR in an Oxisol cultivated for four years in no-tillage system at FEIS/UNESP. The attributes PR and yield were determined in a regular grid with 119 sample points. The PR was determined in the layers of 0-0.05, 0.05-0.10, 0.10-0.15, 0.15-0.20 and 0.25-0.30 m. The results were submitted to procedures of descriptive statistics, linear correlation and geostatistic analysis. The linear correlation between the yield and PR was practically null, as in all soil layers investigated it showed determination coefficients (R2) smaller than 0.03 and not significant. The geostatistic analysis showed moderate structure of spatial dependency for PR in the layers of 0.05-0.10 and 0.10-0.15 m, and strong for yield; however, the conjugate spatial analysis of such attributes showed no correlation, therefore, the spatial variability of PR did not influence the yield.
Correlation between bean yield and soil penetration resistance under no-tillage
Keywords: Cone index; Geostatistic; Soil compaction; Spatial variability